Evaluasi Biaya Pengembangan Sistem Informasi Pengelolaan Arsip Surat (SIPAS) Menggunakan Function Point dan Object Point (Studi Kasus : PT Sekawan Media Informatika) - Febrina Putri Laksamana; Andi Reza Perdanakusuma; Mochamad Chandra Saputra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Software cost estimation is a process of predicting the effort to develop a software. The basic input of software cost estimation is measurement metric. Projects often delays, over-budget, and do not finish because failure estimate software development costs. PT Sekawan Media Informatika determining the estimated cost based on the number of human resources, the required features, and the complexity of the database based on estimates project manager called Guesstimate. This research explains the allocation of cost estimation, time, and human resources in the development of Archive Letter Management System Information (SIPAS) at PT. Sekawan Media Informatika uses Function Point and Object Point, and project schedule using Gantt Chart based on Work Breakdown Structure. Function Point is a metrics sizing of software functionality based on five types of user functions, External Input, External Output, External Inquire, Internal Logic File, and External Interface File and technical calculation from software development, result in a lower effort estimation of 44 people over 9 days with a total cost of Rp. 34.381.426. Object Point is a software measurement metric based on the number and complexity of an object screen, report, and 3GL component (third generation language) as well as calculate the percentage of reuse and productivity value, result in a large estimated effort of 44 people over 12 days with total cost of Rp. 47.286.499.